THE PROPER LEARNING ENGLISH METHOD FOR CHILDREN WITH CANCER IN INDONESIA CARE FOR CANCER KIDS FOUNDATION JOGJAKARTA (YKAKI JOGJA) - Rizka Dinta Murbaningtyas (UAD TEFL International Conference)
Cancer is a chronic illness that could suffer every people included children. Because of cancer treatment for more than 2 years, some students should postpone their school. Through ‘sekolah-ku’ program, YKAKI Jogja freely gives facility for children getting cancer treatment to continue their study in the hospital and in the shelter home. Children living in YKAKI Jogja were often visited by foreign volunteers and got English literature book donation. They interested in learning English but they felt difficult to use English because English is not their first language. However, the children with cancer have limitation in Learning English caused by: 1) side effect of chemotherapy, 2) less self-confident, 3) less support from their family. The research aimed at finding out the proper learning method to teach English for children with cancer in YKAKI Jogja. The research methods used direct observation and interview in order to gain the research data. In the English class, the researcher used bilingual communication with students and created comfort situation in the ward. Some learning methods were applied during learning English such as playing games, watching English videos, and storytelling. The result of this research showed that the children was more motivated to study English when the researcher combined two of three learning methods in the English class than used one method in that class.